Experimental validation and CFD simulation of a Gas-Liquid Cylindrical Cyclone (GLCC©) (2017)
This article constitutes an experimental and CFD simulation study of the separation performances of a Gas-Liquid Cylindrical Cyclone (GLCC) separator. The Oil & Gas industry has shown great interest in the GLCC because of their versatility and cost effectiveness compared to the conventional vessel-type separator. The aim of this study is to improve the understanding of the effects of the dynamic viscosity and surface tension of the liquid phase in the flow hydrodynamics and performance of the GLCC. To accomplish this, it was used three different liquid substances (mineral oil, ISOPAR L and water). The experimental data have been acquired including flow visualization and the amount of the Liquid Carry-Over (LCO) in the gas outlet stream. In the CFD simulation, the RST turbulence model was chosen for the prediction of the hydrodynamics behavior inside the GLCC because of the good agreement with the LCO experimental data (error < 25%). The increase of the viscosity and the reduction of the surface tension shows a reduction of the GLCC efficiency. The increase of viscosity rises the viscous dissipation energy that deforms the helical shape and generates a strong swirl decay in the downstream region. The reduction of the surface tension generates a weaker and longer wave-length of the helical shape whit less defined region for the upward flow and low-pressure zone in the vortex core